The Use of Waste Plastic as a Partial Substitution Aggregate in Asphalt Concrete Pavement - Aschuri, Imam; Yamin, Anwar; Widyasih, Yoseba Dani (Jurnal Teknik Sipil, 2016)
Abstract. As a developing country, Indonesia faces serious problems managing solid waste such as plastic. Annually, Indonesia produces approximately 5.4 million tons of waste plastic, accounting for 14% of the countryâs total solid waste production. Using waste plastic as a partial substitution aggregate in asphalt concrete pavement would be one of solutions for reducing environmental problems from the high volume of waste plastic. Previous studies show that it may be possible to use waste plastic in road pavement to improve the engineering performance of road pavement and increase its service life. This study investigates the performance of asphalt concrete mixtures containing varying amounts of waste plastic as a partial aggregate substitution as compared to that of conventional mixtures. The waste plastic used in this study was chopped into small pieces of approximately passing sieve number 30 and retained sieve number 40, which would replace (by weight) a portion of the mineral aggregates. All mixtures were prepared using 5.82% optimum bitumen content. The performance of asphalt concrete characteristics was studied using the Marshall test, The Indirect Tensile Strength (ITS) test, The Indirect Tensile Stiffness Modulus (ITSM) test, and the Cantabro Loss (CL) test in terms of strength, stiffness modulus, and durability characteristics. In general, laboratory results showed that asphalt concrete mixtures containing waste plastic have higher performance than conventional asphalt concrete mixtures.Abstrak. Sebagai negara berkembang, Indonesia menghadapi masalah serius dalam mengelola sampah padat seperti plastik. Setiap tahun, Indonesia memproduksi sekitar 5,4 juta ton sampah plastik, akuntansi untuk 14% dari total produksi sampah negara. Pemanfaatan sampah plastik sebagai pengganti agregat sebagian di campuran perkerasan aspal beton akan menjadi salah satu solusi untuk mengurangi masalah lingkungan dari tingginya volume sampah plastik. Penelitian sebelumnya menunjukkan bahwa dimungkinkan untuk menggunakan sampah plastik di perkerasan jalan untuk meningkatkan kinerja perkerasan jalan dan umur pelayanan jalan. Studi ini mengkaji kinerja campuran aspal beton yang mengandung berbagai variasi jumlah sampah plastik sebagai pengganti agregat sebagian yang dibandingkan dengan yang campuran konvensional. Sampah plastik yang digunakan dalam penelitian ini berukuran kecil yang lolos saringan nomor 30 dan tertahan di saringan nomor 40, yang akan menggantikan (berat) sebagian dari agregat mineral. Semua campuran disiapkan menggunakan 5,82% kadar aspal optimum. Kinerja karakteristik aspal beton dikaji menggunakan uji Marshall, uji kekuatanÂ  tarik tak langsung (ITS), uji modulus kekakuan tarik tak langsung (ITSM), dan uji Cantabro Loss (CL) yang dikaitkan dengan kekuatan, modulus kekakuan, dan karakteristik durabilitas. Secara umum, hasil laboratorium menunjukkan bahwa campuran aspal beton yang mengandung limbah plastik memiliki kinerja lebih tinggi dari campuran beton aspal konvensional.